2013
DOI: 10.1021/es400726e
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Stable Isotopes in Primary Uptake Compartments Across Streams Differing in Nutrient Availability

Abstract: High variability in the natural abundance of nitrogen stable isotopes (δ(15)N) has been reported for primary uptake compartments (PUCs; e.g., epilithon, filamentous algae, bryophytes, macrophytes) in human-impacted aquatic ecosystems, but the origin of this variability is not yet well understood. We examined how δ(15)N of different PUC types relate to δ(15)N of dissolved inorganic nitrogen (DIN) species (nitrate and ammonium) and to the stream nutrient concentrations in which they grow. We selected 25 reaches … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 47 publications
5
26
0
1
Order By: Relevance
“…Our results showed that variability in aquatic plant δ 15 N signatures were mainly influenced by extrinsic factors (e.g., geomorphological type and land use) as observed for aquatic plants from stream ecosystems (Pastor et al., ; Peipoch, Gacia, Pastor, et al., ). Basin land use and human disturbances associated with the different land uses are major factors determining variability in δ 15 N signatures of DIN, consequently, δ 15 N in aquatic plants may respond to this variability since DIN is the major N source for them (e.g., Cole, Kroeger, Mcclelland, & Valiela, ; Pastor et al., ; Peipoch, Martí, & Gacia, ).…”
Section: Discussionsupporting
confidence: 68%
“…Our results showed that variability in aquatic plant δ 15 N signatures were mainly influenced by extrinsic factors (e.g., geomorphological type and land use) as observed for aquatic plants from stream ecosystems (Pastor et al., ; Peipoch, Gacia, Pastor, et al., ). Basin land use and human disturbances associated with the different land uses are major factors determining variability in δ 15 N signatures of DIN, consequently, δ 15 N in aquatic plants may respond to this variability since DIN is the major N source for them (e.g., Cole, Kroeger, Mcclelland, & Valiela, ; Pastor et al., ; Peipoch, Martí, & Gacia, ).…”
Section: Discussionsupporting
confidence: 68%
“…There is a strong need therefore for an accurate, practical and fast environmental monitoring tool. In marine, coastal, transitional water and lotic ecosystems, macroalgal and epilithic δ 15 N signatures have proved to be successful in determining the types and space-time variability of nitrogen loads (Bentivoglio et al, 2016;Cejudo et al, 2014;Cole et al, 2004;Dailer et al, 2010;Gartner et al, 2002;Jona-Lasinio et al, 2015;Orlandi et al, 2014, Pastor et al, 2013Peipoch et al, 2012;Schiller et al, 2009;Titlyanov et al, 2011;Vizzini et al, 2005), while in lacustrine ecosystems there is a lack of knowledge concerning epilithic δ 15 N signatures.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been performed on macroalgal δ 15 N signatures in marine coastal ecosystems (Cole et al, 2004;Dailer et al, 2010;Gartner et al, 2002;Titlyanov et al, 2011) and coastal brackish lakes (Jona-Lasinio et al, 2015) and lagoons (Vizzini et al, 2005). Recent studies have applied stable isotope analysis to epilithic δ 15 N signatures to evaluate the effect of anthropic land use on rivers (Bentivoglio et al, 2016;Cejudo et al, 2014;Pastor et al, 2013Pastor et al, , 2014Peipoch et al, 2012;Schiller et al, 2009). However, in spite of its widespread presence, epilithon is poorly understood as an ecological indicator of nitrogen pollution.…”
Section: Introductionmentioning
confidence: 99%
“…These increases in dissolved NO 3 − and NH 4 + likely increase the isotopic values of dissolved inorganic nitrogen (DIN) in the water column of invaded habitats. Pastor et al (2013) showed that the δ 15 N values of DIN (particularly, NH 4 + ) are strongly correlated with the δ 15 N values of primary producers, which assimilate DIN species and pass these isotopic fingerprints to herbivores and other aquatic consumers (Vander Zanden et al, 2005).…”
Section: Tablementioning
confidence: 99%